REVITALIZING TRADITIONAL KNOWLEDGE OF RICE MANTRAS AS AN ECOPEDAGOGICAL MEDIUM IN PRIMARY SCHOOL EDUCATION - Supriadi, Supriadi; Mattalatta, Solihin; Firmansyah, Andi; Saifullah, Aceng Ruhendi; Mubarok, Yasir; Sani, Amar (JMIE (Journal of Madrasah Ibtidaiyah Education), 2025)
This study examines the Makassarese rice mantras (doangang padi) as a culturally embedded learning resource for primary education within an ecopedagogical framework. The research was conducted in Lantang Village, Polongbangkeng Utara District, Takalar Regency, South Sulawesi, focusing on the integration of traditional ecological knowledge into school learning. Using a qualitative descriptive approach, data were collected through direct field observation, in-depth interviews with two customary leaders and seven community members aged 48 - 72 years who are proficient in jammang riolo (traditional Makassar language), and documentation of local manuscripts. This process aimed to interpret the mantras accurately from Makassarese into Indonesian and validate their meaning. School observations were also carried out to assess the readiness of teachers and the needs of students in implementing local knowledge-based materials. Data were analyzed using an ecopedagogical perspective, identifying ecological, spiritual, and social values that could be conserved as educational content. The findings reveal that the rice mantras contain explicit messages on planting cycles, water conservation, biodiversity, gratitude, cooperation, and responsibility. These values were applied in the classroom through mini rice-planting projects, visual storytelling, and local vocabulary booklets. Such integration enhanced students’ moral knowing dimensions perspective-taking, moral reasoning, decision-making, and self-knowledge while reinforcing cultural identity, ecological awareness, and collaborative spirit. The study concludes that tradition-based teaching offers a strategic, contextually relevant model for character-oriented and environmentally conscious primary education.